2023
DOI: 10.3390/ijms241310986
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fibrotic Effects of RF Electric Currents

Abstract: Hypertrophic scars and keloids are two different manifestations of excessive dermal fibrosis and are caused by an alteration in the normal wound-healing process. Treatment with radiofrequency (RF)-based therapies has proven to be useful in reducing hypertrophic scars. In this study, the effect of one of these radiofrequency therapies, Capacitive Resistive Electrical Transfer Therapy (CRET) on biomarkers of skin fibrosis was investigated. For this, in cultures of human myofibroblasts treated with CRET therapy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Additionally, Tecar therapy action was assessed on biomarkers of skin fibrosis using human myofibroblast cultures. Results indicated that it decreased the expression of extracellular matrix proteins, altered metalloproteinase 9 expression, and reduced nuclear factor kappa-light-chain-enhancer of activated B cells activation compared to controls, suggesting its potential efficacy in treating fibrotic conditions [163].…”
Section: Tecar Therapymentioning
confidence: 99%
“…Additionally, Tecar therapy action was assessed on biomarkers of skin fibrosis using human myofibroblast cultures. Results indicated that it decreased the expression of extracellular matrix proteins, altered metalloproteinase 9 expression, and reduced nuclear factor kappa-light-chain-enhancer of activated B cells activation compared to controls, suggesting its potential efficacy in treating fibrotic conditions [163].…”
Section: Tecar Therapymentioning
confidence: 99%